UHPLC-QQQ-MS and RP-HPLC Detection of Bioactive Alizarin and Scopoletin Metabolites from Morinda citrifolia Root Extracts and Their Antitubercular, Antibacterial, and Antioxidant Activities - Sam-Ang P. (2023)
Morinda citrifolia is a medicinal plant that has been traditionally used in various therapeutic applications. All parts of M. citrifolia including fruits, leaves, stems, roots, and flowers contain various biologically active phytochemicals. This study aimed to evaluate the antitubercular, antibacterial, and antioxidant activities of M. citrifolia root extracts and spectroscopically analyze the bioactive metabolites. M. citrifolia root extracts were prepared via maceration. The minimum inhibitory concentration (MIC) for antitubercular activity, the inhibition zone for antibacterial activity, and the antioxidant activities in terms of half-maximal inhibitory concentration (IC50) values were determined. 1H-NMR, RP-HPLC, and UHPLC-QQQ-MS analyses were performed to evaluate the secondary metabolites. The results showed that the dichloromethane root extract exhibited relatively good inhibition of M. tuberculosis with an MIC value of 50 μg/mL. All extracts were mostly active against five tested bacterial strains. The ethanolic and dichloromethane root extracts showed the highest antioxidant power against DPPH (IC50 = 0.82 mg/mL) and NO (IC50 = 0.64 mg/mL) radicals, respectively. The 1H-NMR-based screening of the secondary metabolites of all M. citrifolia root extracts confirmed the presence of triterpenes, steroids, phenolics, flavonoids, tannins, and anthraquinones as major bioactive components. Alizarin and scopoletin were detected in the extracts via UHPLC-QQQ-MS, and the alizarin (0.552-3.227 g/100 g dry weight) and scopoletin (0.092-0.554 g/100 g dry weight) contents were quantified via RP-HPLC. The antimicrobial and antioxidant activities of M. citrifolia root extracts and the identification of the main bioactive ingredients are the initial studies that can be beneficial for further in vivo studies and biomedical applications of its bioactive compounds.